Observations on Language - Grammar Metaphors and Thinking Patterns - Dilek PEÇENEK (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
According to the Conceptual Metaphor Theory the thinking processes rely on metaphors. Conceptual metaphor includes a comprehension of one experience domain through different experience domains. Accordingly, conceptual metaphors are perceived as a mapping from one source domain to the target domain. We experience objects according to metaphors and we speak by utilizing metaphors. Namely, conceptual metaphors produce linguistic metaphors. Due to metaphors’ roles as structuring and conveying thinking domains, Metaphor Analysis is seen as an effective research tool that brings out individuals’ ways of conceptualization and their views. In this study metaphor analysis on language and grammar has been employed so as to find out the cognition and opinion patterns of graduate students studying linguistics and foreign language-literature. The data are gathered via metaphor elicitation survey developed within the frame of experimental metaphor elicitation technique, and are analyzed through content analysis. Accordingly, the salient language and grammar metaphors are attained on the basis of linguistic metaphors (LANGUAGE IS A TOOL, GRAMMAR IS ANIMATE...). Depending on the specified conceptual metaphors and entailments, thinking proposals on language and grammar are tried to be inferred. It is seen that the participants embody language and grammar with the concrete concepts and their features.